SV2A PET shows hippocampal synaptic loss in cognitively unimpaired APOE ε4/ε4 homozygotes - Snellman, Anniina; Tuisku, Jouni; Koivumäki, Mikko; Wahlroos, Saara; Aarnio, Richard; Rajander, Johan; Karrasch, Mira; Ekblad, Laura L.; Rinne, Juha O. (WILEY, 2025)
Introduction: We investigated hippocampal synaptic density using synaptic vesicle 2A positron emission tomography (PET), and its association with amyloid beta (Aβ) and cognitive performance in healthy apolipoprotein E (APOE) ε4 carriers.
Methods: Synaptic density was assessed in 46 individuals (APOE ε4/ε4 n = 14; APOE ε3/ε4 n = 16; APOE ε3/ε3 n = 16) with [11C]UCB-J-PET standardized uptake value ratios (SUVRs), by using the centrum semiovale as a reference region. Differences in hippocampal [11C]UCB-J SUVRs were analyzed with analysis of variance (ANOVA) and linear models. Associations among [11C]UCB-J SUVR, Aβ, hippocampal volume, and cognitive variables were analyzed with Spearman correlation.
Results: Hippocampal synaptic density was different among the APOE groups (PANOVA = 0.016): APOE ε4/ε4 carriers had lower [11C]UCB-J SUVRs compared to APOE ε3/ε3 (p = 0.013). Hippocampal synaptic density did not correlate with Consortium to Establish a Registry for Alzheimer's Disease (CERAD) total score (rho = -0.052, p = 0.74), Alzheimer's Prevention Initiative Preclinical Cognitive Composite (APCC) score (rho = 0.17, p = 0.28), or [11C]PiB uptake (rho = -0.10, p = 0.50).
Discussion: Hippocampal synaptic loss emerges early in the AD continuum and is measurable in vivo in cognitively unimpaired high-risk individuals.
Highlights: Synaptic density was studied in vivo in healthy older adults using [11C]UCB-J positron emission tomography. Apolipoprotein E (APOE) ε4/ε4 carriers had lower hippocampal synaptic density compared to APOE ε3/ε3. Synaptic density was not associated with cognitive performance in this population. Hippocampal synaptic alterations occur before clinical symptoms in APOE ε4/ε4 carriers.